Identification of Five Hub Genes Based on Single-Cell RNA Sequencing Data and Network Pharmacology in Patients With Acute Myocardial Infarction - Song, Ziguang; Gao, Pingping; Zhong, Xiao; Li, Mingyang; Wang, Mengmeng; Song, Xiang (Frontiers in Public Health, 2022)
Acute myocardial infarction (AMI) has a high mortality. Single-cell RNA sequencing (scRNA-seq) analyzed disease heterogeneity of disease at single-cell level. From the Gene Expression Omnibus (GEO) database (GSE180678), AMI scRNA-seq were downloaded and preprocessed by Seurat package. Gene expression data came from GSE182923. Cell cluster analysis was conducted. Cell types were identified. KEGG (Kyoto Encyclopedia of Genes and Genomes) and GO (Gene Ontology) analyses were performed on hub genes. Drugs was predicted by PPI and Molecular docking. 7 cell clusters were defined based on the scRNA-seq dataset, and the clusters were labelled as 5 cell types by marker genes. Hematopoietic stem cell type as a differential subgroups were higher in AMI than healthy tissues. 52 common genets were identified from available databases and PPI analysis. Base on 52 genes, 5 Clusters were obtained using MCODE algorithm, and genes in 5 Clusters involved in immune and inflammatory pathways were determined. Correlation analysis showed that hematopoietic stem cell type were negatively correlated with ATM, CARM1 and CASP8 but positively correlated with CASP3, PPARG. This was reversed with immune cells. Molecular docking analysis showed that DB05490 had a lowest docking score with PPARG. We identified 5 hub genes (ATM, CARM1, CASP8, CASP3, PPARG) involved AMI progression. Compound DB05490 was a potential inhibitor of PPAG.